High versus low fixed-dose four factor-prothrombin complex concentrate for warfarin reversal in patients with intracranial hemorrhage. (October 2022) - Compton, Frances; Hall, Jeremy; De Simone, Nicole; Usmani, Amena; Sarode, Ravi; Burner, James
Abstract: Background: Four-factor prothrombin complex concentrate 4F-PCC is the standard of care for warfarin reversal in patients with major bleed or requiring urgent surgery. Although the 4F-PCC dose is weight and international normalized ratio (INR) based, for practical purposes, a fixed-dose approach has been explored, especially for rapid reversal. We report our experience using two different fixed-dose 4F-PCC for warfarin reversal in patients presenting with intracranial hemorrhage (ICH). Study design and methods: We completed a retrospective chart review comparing high (4000 units) versus low (2000 units) dose 4F-PCC by evaluating patient characteristics, laboratory data, and pre-and post-4F-PCC brain imaging. Results: There was no significant difference between patient characteristics or INR correction (≤1.5) between the two groups. Eighty percent (12/15) of patients who received the low dose 4F-PCC had either improved or stable brain imaging as compared to 88% (14/16) of patients who received the high dose PCC. When the eight patients (4 from each arm of the study) who required neurosurgery were excluded, only two patients in each arm had worse imaging after 4F-PCC. Conclusion: There was no significant difference between the INR correction and the brain imaging changes in patients with an ICH who received either the high or the low fixed-dose 4F-PCC for warfarin reversal.